Leadership Style and Employees' Commitment to Service Quality: An Analysis of the Mediation Pathway via Knowledge Sharing - Pahi, Munwar Hussain; Abdul-Majid, Abdul-Halim; Fahd, Samar; Gilal, Abdul Rehman; Talpur, Bandeh Ali; Waqas, Ahmad; Anwar, Toni (Frontiers in Psychology, 2022)
Very little attention has been given to understanding the commitment to service quality and desirable outcomes in the hotel industry. This study investigates the impact of directive and participative leadership on the frontline commitment to service quality through the mediation of knowledge sharing. This will eventually help us to generate the employees’ Commitment to Service Quality (CSQ) desirable behavior. The survey was distributed to 37 hotels in Karachi via mail. A total of 235 frontline employees participated in the survey. The study findings show that directive leadership has a negative relationship with a commitment to service quality. On the other hand, participative leadership positively influences the commitment to service quality. Notably, knowledge sharing mediated between directive, participative, and commitment to service quality. The positive linkage between commitment to service quality and desirable outcomes, job performance OCB and negative relation to turnover intention.